Proceedings of the 26th Annual Computer Security Applications Conference 2010
DOI: 10.1145/1920261.1920268
|View full text |Cite
|
Sign up to set email alerts
|

Fast and practical instruction-set randomization for commodity systems

Abstract: Instruction-set randomization (ISR) is a technique based on randomizing the "language" understood by a system to protect it from code-injection attacks. Such attacks were used by many computer worms in the past, but still pose a threat as it was confirmed by the recent Conficker worm outbreak, and the latest exploits targeting some of Adobe's most popular products. This paper presents a fast and practical implementation of ISR that can be applied on currently deployed software. Our solution builds on a binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 23 publications
0
41
0
1
Order By: Relevance
“…Of course, changing the order of instruction storing must ensure that the topology order of execution is maintained or the results are unchanged. [30] presented the basic-block granularity randomization, [31] presented the basic-block's internal instruction granularity randomization.…”
Section: Address Space Layout Randomizationmentioning
confidence: 99%
“…Of course, changing the order of instruction storing must ensure that the topology order of execution is maintained or the results are unchanged. [30] presented the basic-block granularity randomization, [31] presented the basic-block's internal instruction granularity randomization.…”
Section: Address Space Layout Randomizationmentioning
confidence: 99%
“…Portokalidis et al [15] use a similar approach to RISE, based on the Intel PIN dynamic binary rewriting tool. They use a database of keys, to randomize every loaded code image in a different way.…”
Section: F Related Permutation Workmentioning
confidence: 99%
“…However, lately systems' security have been highly enhanced by introducing different solutions [2,3] either at operating system or at application layer works, malware detection as a part of it is still an on-going and challenging research problem. Various research works [4,5] have shown that not only malicious software (malware) can get access to private information but also goodware might try to invade to users' digital space as it is considered the main asset for digital business in this new era, and consequently can threaten their private sphere.…”
Section: Introductionmentioning
confidence: 99%